1997
DOI: 10.1007/s004670050341
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in pediatric patients with idiopathic hypercalciuria

Abstract: It is well known that some patients with renal lithiasis due to idiopathic hypercalciuria (IH) may exhibit decreased bone mineral density (BMD). We have studied a large group of children with IH and related their BMD values to several renal function parameters and calcium and bone metabolism markers. Children with IH had higher osteocalcin and calcitriol levels and higher urinary excretion of magnesium and prostaglandin E2, as well as lower tubular reabsorption of phosphate, urinary excretion of ammonium, maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
3
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 33 publications
8
60
3
5
Order By: Relevance
“…One of the more important questions to be answered is whether adult osteoporosis is initiated during childhood in children with IH due to a failure in reaching adult peak bone mass values. In a previous study, our group determined that 30% of the 73 hypercalciuric children investigated showed signs of osteopenia [2]. This association of osteopenia and IH was later confirmed by Freundlich et al [3], Penido et al [4], and Schwaderer et al [5], who respectively reported that 38, 37, and 47% of the IH children studied showed a significant decrease in BMD.…”
Section: Introductionsupporting
confidence: 70%
“…One of the more important questions to be answered is whether adult osteoporosis is initiated during childhood in children with IH due to a failure in reaching adult peak bone mass values. In a previous study, our group determined that 30% of the 73 hypercalciuric children investigated showed signs of osteopenia [2]. This association of osteopenia and IH was later confirmed by Freundlich et al [3], Penido et al [4], and Schwaderer et al [5], who respectively reported that 38, 37, and 47% of the IH children studied showed a significant decrease in BMD.…”
Section: Introductionsupporting
confidence: 70%
“…The prevalence of this disorder in children with IH has been estimated to be up to 38% [6]. In a previous study we reported diminished BMD at the spinal site in 30% of patients [5], whereas in the present study, a Z-score <–1 was found in 42.5% of girls with IH. With respect to the mothers in our study, all had IH.…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies in the last few years have also reported a reduction of BMD in pediatric patients with IH [5, 6, 7]. Although it is well documented that environmental factors contribute to BMD, family studies have shown that genetic factors may also play an important role in determining bone mass [8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…However, alterations in childhood bone mass acquisition may not affect bone mass many decades later in late adulthood because there is a homeostatic system that tends to return to a set point after any transient perturbation [52] . Thus, workup of idiopathic hypercalciuria necessarily involves the investigation of bone mineral metabolism and the characterization of the profile of bone changes, so the physician can act objectively in prevention and treatment [40,42,43,53] . Obesity associated with metabolic syndrome is a known risk factor for UL in adults, however, this association is not well established in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%